2018
DOI: 10.1021/acs.jpcc.8b09184
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Coherent Spectroscopy of Complex Molecular Systems in Solution

Abstract: An understanding of microscopic interactions in solution is of fundamental importance in chemistry. However, the structure and dynamics of complex systems in the condensed phase, especially far from thermal equilibrium, are masked by broad and often featureless absorption and emission spectra. Nonlinear optical spectroscopy has proven to be a powerful and general approach to disentangling congested spectra by spreading information across multiple dimensions, revealing features oftentimes hidden in lower-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…With the one-sided CW pulse EOM-PMA, one can perform 21 propagations of the auxiliary DMs in time t and compute P k (ω τ , τ′, T , T ′, t ) for fixed ω τ or I 3 D (ω τ , τ′, ω t , T , T ′) for fixed ω τ and τ′. Fifth-order two-quantum 2D, three-quantum 2D, and 8WM 4D signals can also be treated in a similar manner.…”
Section: Equation-of-motion Phase-matching Approach (Eom-pma) For Non...mentioning
confidence: 99%
“…With the one-sided CW pulse EOM-PMA, one can perform 21 propagations of the auxiliary DMs in time t and compute P k (ω τ , τ′, T , T ′, t ) for fixed ω τ or I 3 D (ω τ , τ′, ω t , T , T ′) for fixed ω τ and τ′. Fifth-order two-quantum 2D, three-quantum 2D, and 8WM 4D signals can also be treated in a similar manner.…”
Section: Equation-of-motion Phase-matching Approach (Eom-pma) For Non...mentioning
confidence: 99%
“…Abundant research has identified the important roles of vibrational coherences in important natural processes, including in the photoisomerization of retinal that is responsible for vision, exciton transport in light-harvesting complexes, excited state proton transport in the green fluorescent protein, and a variety of charge transport materials. However, many researchers have provided pertinent counterarguments to the functional role of these vibrational coherences, particularly with respect to the photosynthetic light-harvesting complex. Worse yet, identifying the influence of molecular vibrations on photochemistry can be quite complicated, especially for complex systems in which energy can be partitioned over many possible pathways. Discerning the direct role of vibrations and phonons in photochemical reactivity requires further investigation.…”
mentioning
confidence: 99%